PENINGKATKAN KINERJA GURU MELALUI SUPERVISI KLINIS - Sukarti Sukarti; Rambat Nur Sasongko; Aliman Aliman (Manajer Pendididikan, 2017)
The objectiveof this research is to describe the management of clinical supervision at Junior High School Number 1 Talang Empat. The subject of the research were principal, teachers and supervisor. The data collected thorught observation, interview, and documentation. The data analysis qualitative used the analysis of Milles and Huberman. The results generally show that the principal has been trying implementation of clinical supervision in improving the performance of teacher teaching at Junior High School Number 1 Talang Empat.